Development of 2" AlN Substrates Using SiC Seeds - Avdeev, O.V.; Chemekova, T.Yu.; Mokhov, E.N.; Nagalyuk, S.S.; Helava, H.; Ramm, M.G.; Segal, A.S.; Zhmakin, A.I.; Makarov, Yu.N. (IntechOpen, 2012)
None